Stellate ganglion, inflammation, and arrhythmias: a new perspective on neuroimmune regulation - Lei, Qiulian; Jiang, Zefei; Shao, Yu; Liu, Xinghong; Li, Xiaoping (Frontiers in Cardiovascular Medicine, 2024)
Current research on the stellate ganglion (SG) has shifted from merely understanding its role as a collection of neurons to recognizing its importance in immune regulation. As part of the autonomic nervous system (ANS), the SG plays a crucial role in regulating cardiovascular function, particularly cardiac sympathetic nerve activity. Abnormal SG function can lead to disordered cardiac electrical activity, which in turn affects heart rhythm stability. Studies have shown that excessive activity of the SG is closely related to the occurrence of arrhythmias, especially in the context of inflammation.Abnormal activity of the SG may trigger excessive excitation of the sympathetic nervous system (SNS) through neuroimmune mechanisms, thereby increasing the risk of arrhythmias. Simultaneously, the inflammatory response of the SG further aggravates this process, forming a vicious cycle. However, the causal relationship between SG, inflammation, and arrhythmias has not yet been fully clarified. Therefore, this article deeply explores the key role of the SG in arrhythmias and its complex relationship with inflammation, providing relevant clinical evidence. It indicates that interventions targeting SG function and inflammatory responses have potential in preventing and treating inflammation-related arrhythmias, offering a new perspective for cardiovascular disease treatment strategies.